2022
DOI: 10.1039/d1sc05932g
|View full text |Cite
|
Sign up to set email alerts
|

Arene–perfluoroarene interactions confer enhanced mechanical properties to synthetic nanotubes

Abstract: Supramolecular nanotubes prepared through macrocycle assembly offer unique properties that stem from their long-range order, structural predictability, and tunable microenvironments. However, assemblies that rely on weak non-covalent interactions often have...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 39 publications
(45 reference statements)
0
12
0
Order By: Relevance
“…Conjugated π-electron systems of nanostructured aromatic macrocycles are of peculiar interests in synthetic organic chemistry because they exceptionally show the unique cyclic π conjugation with either a parallel or radial orientation of p z orbitals. Various topologically remarkable structures have been afforded by their contorted π-systems which, in turn, induced enduring attractions in optoelectronic materials and supramolecular assemblies. Merging the concept of molecular chirality with π-conjugated macrocyclic chemistry has recently been revitalized for emergent applications in chiral sensing, enantioselective encapsulation, three-dimensional (3D) displays, and chiroptical materials. Despite this much attention, access to the structurally strained and rigid chiral frameworks has long been considerably challenging. Previous studies revealed that the open-chain analogues were extensively explored as the chirality could be achieved on molecular level or in the aggregated phases of assembled superstructures .…”
Section: Introductionmentioning
confidence: 99%
“…Conjugated π-electron systems of nanostructured aromatic macrocycles are of peculiar interests in synthetic organic chemistry because they exceptionally show the unique cyclic π conjugation with either a parallel or radial orientation of p z orbitals. Various topologically remarkable structures have been afforded by their contorted π-systems which, in turn, induced enduring attractions in optoelectronic materials and supramolecular assemblies. Merging the concept of molecular chirality with π-conjugated macrocyclic chemistry has recently been revitalized for emergent applications in chiral sensing, enantioselective encapsulation, three-dimensional (3D) displays, and chiroptical materials. Despite this much attention, access to the structurally strained and rigid chiral frameworks has long been considerably challenging. Previous studies revealed that the open-chain analogues were extensively explored as the chirality could be achieved on molecular level or in the aggregated phases of assembled superstructures .…”
Section: Introductionmentioning
confidence: 99%
“…(D) Probing the impacts of arene–perfluoroarene interactions on nanotube mechanical strength. Adapted and reprinted with permission from refs , , and . Copyrights 2018 NAS, 2019 John Wiley and Sons, and 2022 Royal Society of Chemistry, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…After developing a general approach to macrocyclization and 1D assembly, which enabled the high-yielding synthesis of many different macrocycles, we recognized an opportunity to further augment cohesive energies between macrocycles by installing additional noncovalent interactions. Specifically, we prepared pentagonal macrocycles from PDA and 2,3,5,6-tetrafluoroterephthalaldehyde (F 4 –PDA) and mixed them in a 1:1 ratio to invoke quadrupolar arene-perfluoroarene (AP) interactions within the macrocycle assemblies . First, we noticed that nanotubes prepared from mixed macrocycle systems were more crystalline than F 4 –PDA or PDA macrocycles alone because of the AP interactions that reinforced the structure.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Reaching inner pore diameters that are smaller and better defined, more compatible with molecular dimensions, requires other strategies that make use of more sophisticated molecules and directional noncovalent interactions. For instance, covalent macrocycles can be made to orderly stack on top of each other, often aided by peripheral H-bonding units, to form cylindrical structures with well-defined pores (Figure a, left). Alternatively, relatively flexible linear oligomers can be made to fold intramolecularly into helical structures ( i . e ., foldamers; Figure a, right), which can also present available internal channels.…”
Section: Introductionmentioning
confidence: 99%